The Emerging Nature of Astrocyte Diversity - Baljit S. Khakh; Benjamin Deneen (2019)
Astrocytes are morphologically complex, ubiquitous cells that are viewed as a homogeneous population tiling the entire central nervous system (CNS). However, this view has been challenged in the last few years with the availability of RNA sequencing, immunohistochemistry, electron microscopy, morphological reconstruction, and imaging data. These studies suggest that astrocytes represent a diverse population of cells and that they display brain area– and disease–specific properties and functions. In this review, we summarize these observations, emphasize areas where clear conclusions can be made, and discuss potential unifying themes. We also identify knowledge gaps that need to be addressed in order to exploit astrocyte diversity as a biological phenomenon of physiological relevance in the CNS. We thus provide a summary and a perspective on astrocyte diversity in the vertebrate CNS.